A DEIXIS ANALYSIS OF SONG LYRICS IN “I WANT TO BREAK FREE” BY QUEEN - Sutrisno Saputra; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2021)
A Deixis Analysis of Song Lyrics in Queen “I Want to Break Free”. The aim of the research are to analyze the three types of deixis analysis using Yule (1996) theory and to identify the dominant deixis found in the lyrics. Researchers chose this song as the subject of analysis because of the song's popularity and it also consisted of deictic words and reference meanings. This study was conducted by using descriptive qualitative method. The data this research are lyrics of “I want to break free” song by Queen. In addition, this song was classified into three types of deixis analysis based on their own criteria. The result of the research showed that there are three types of deixis found in the song. They are: Person deixis (94%), Spatial deixis: (3%), Temporal deixis: (3%). In addition, the highest percentage of all is Person deixis. It means that the use of personal deixis indicated the participant in this song.  Keywords:  Analysis, Deixis, Song, Lyrics